Environmental health issues and the solution in Indonesia: A narrative review - Fatimah, Mustika; Sunarsih, Elvi; Sitorus, Rico Januar; Nurhayati, Nurhayati (Science Midwifery, 2024)
Indonesia is a rich country in natural resources but also vulnerable to environmental degradation. Factors such as rapid urbanization, industrialization, and intensive agriculture have led to serious environmental degradation. Holistic and sustainable solutions are needed, requiring further support. The aim of this narrative review is to present various environmental health issues and the solution in Indonesia that can effectively build awareness, motivate action, and guide more sustainable environmental restoration efforts. This study uses a narrative review method. The literature review was conducted through PubMed NCBI and ScienceDirect databases. Keywords used include “Environmental Health Issues And Solutions In Indonesia” AND/OR “Environmental Health Issues In Indonesia and Their Solutions”. The criteria for articles in this study are that they must be in English, full text, open access, research articles or review articles, with results and discussions related to environmental health issues in Indonesia along with their solutions, and published within the last 10 years (2012-2022). We found 11 articles that discuss these topics. In the intricate tapestry of Indonesia's environmental landscape, the harmonious interplay of governmental, industrial, and communal efforts, guided by robust policies and inclusive engagement, weaves the threads of sustainability and resilience into the fabric of the nation's future.